Parathyroid hormone 1-34 reduces dexamethasone-induced terminal differentiation in human articular chondrocytes. (10th August 2016) - Chang, Ling-hua; Wu, Shun-Cheng; Chen, Chung-Hwan; Wang, Gwo-Jaw; Chang, Je-ken; Ho, Mei-Ling
Highlights: Dex induces terminal differentiation of human articular chondrocytes. PTH 1-34 treatment reduces Dex-induced terminal differentiation and apoptosis of articular chondrocytes. PTH 1-34 treatment may protect articular cartilage from further damage when received Dex administration. Abstract: Intra-articular injection of dexamethasone (Dex) is occasionally used to relieve pain and inflammation in osteoarthritis (OA) patients. Dex induces terminal differentiation of chondrogenic mesenchymal stem cells in vitro and causes impaired longitudinal skeletal growth in vivo. Parathyroid hormone 1-34 (PTH 1-34) has been shown to reverse terminal differentiation of osteoarthritic articular chondrocytes. We hypothesized that Dex induces terminal differentiation of articular chondrocytes and that this effect can be mitigated by PTH 1-34 treatment. We tested the effect of Dex on terminal differentiation in human articular chondrocytes and further tested if PTH 1-34 reverses the effects. We found that Dex treatment downregulated chondrogenic-induced expressions of SOX-9, collagen type IIa1 ( Col2a1 ), and aggrecan and reduced synthesis of cartilaginous matrix (Col2a1 and sulfated glycosaminoglycan) synthesis. Dex treatment upregulated chondrocyte hypertrophic markers of collagen type X and alkaline phosphatase at mRNA and protein levels, and it increased the cell size of articular chondrocytes and induced cell death. These results indicated that Dex induces terminal differentiation of articular chondrocytes. To test whether PTH 1-34 treatment reverses Dex-induced terminal differentiation of articular chondrocytes, PTH 1-34 was co-administered with Dex. Results showed that PTH 1-34 treatment reversed both changes of chondrogenic and hypertrophic markers in chondrocytes induced by Dex. PTH 1-34 also decreased Dex-induced cell death. PTH 1-34 treatment reduces Dex-induced terminal differentiation and apoptosis of articular chondrocytes, and PTH 1-34 treatment may protect articular cartilage from further damage when received Dex administration.